2023
DOI: 10.1161/jaha.122.027959
|View full text |Cite
|
Sign up to set email alerts
|

Always Look on the Bright Side: Associations of Optimism With Functional Outcomes After Stroke

Abstract: Background Psychological health is as an important contributor to recovery after cardiovascular disease, but the roles of both optimism and depression in stroke recovery are not well characterized. Methods and Results A total of 879 participants in the SRUP (Stroke Recovery in Underserved Populations) 2005 to 2006 Study, aged ≥50 years, with incident stroke admitted to a rehabilitation facility were included. Optimism was assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A recent study found that optimism following stroke was associated with improved recovery, highlighting the importance of the brain-mind-body axis independent of known psychiatric diagnoses [163]. Key to optimizing the brain-mind-body axis is ensuring stroke survivors maintain robust social interactions.…”
Section: Social Interactions and Supportmentioning
confidence: 99%
“…A recent study found that optimism following stroke was associated with improved recovery, highlighting the importance of the brain-mind-body axis independent of known psychiatric diagnoses [163]. Key to optimizing the brain-mind-body axis is ensuring stroke survivors maintain robust social interactions.…”
Section: Social Interactions and Supportmentioning
confidence: 99%